2018
DOI: 10.1590/1809-4430-eng.agric.v38n3p411-416/2018
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal From Swine Wastewater in a Combined Vertical and Horizontal Flow Constructed Wetland System

Abstract: This study aimed to assess the performance of a combined vertical flow (VFCW) and horizontal subsurface-flow (HFCW) constructed wetland systems built on a pilot scale and submitted to different configurations and organic load application rates of pre-treated swine wastewater (SWW) in anaerobic systems on the nitrogen and phosphorus removal.The average values of redox potential in the systems were between anoxic and aerobic conditions, favoring an increased nitrate concentration in VFCW. Nitrogen removal by VFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Concerning the depuration performance of the constructed wetland, the reduction in the pH of SW, which was close to neutrality, was in accordance with Boas et al (2018) [54], who worked on CWs combining H-SSF and V-SSF systems, which favor the microbial activity of OM degradation and nutrient conversion.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Concerning the depuration performance of the constructed wetland, the reduction in the pH of SW, which was close to neutrality, was in accordance with Boas et al (2018) [54], who worked on CWs combining H-SSF and V-SSF systems, which favor the microbial activity of OM degradation and nutrient conversion.…”
Section: Discussionsupporting
confidence: 86%
“…Literature reports COD removal efficiencies in the range of 50-80% [33,35,36,60] with an extreme value of 99.5% detected by Masi et al (2017) [14] working in a CW combined system (as in our study). N removal varies between 60% and 80% according to many authors [3,8,11,27,36,54], but extreme values are also reported (10-40% [33,35] to 99% [14]). In our study, the TKN removal efficiency for the CW system with RR = 4:1 is in the range reported by the majority of studies, and it is not far from the optimal value of [14] in the CW with RR = 10:1.…”
Section: Discussionmentioning
confidence: 99%